Study and Optimization of the Effect of Temperature, Acid Concentration, and Rock Grain Size on the pH of Carbonate Reservoir Acidizing - Amin Ahmadi; Kaveh Paydar; Ali Ebadi; Mehrdad Manteghian (Journal of Chemical and Petroleum Engineering, 2022)
After the carbonate reservoir acidizing and the damaged wellbore stimulating, the pH of the environment has particular importance in reducing corrosion during production. In this study, the pH change after the calcium carbonate and hydrochloric acid reaction was modeled, and the optimum pH after the reaction was determined. Also, the effect of temperature HCl concentration and calcium carbonate grain size on final pH was investigated. According to the findings, an increase in temperature causes an increase in final pH. The effect of concentration is against temperature, and pH decreases with increasing concentration. Also, the grain size of calcium carbonate particles has an insignificant effect on pH alteration. Hence, the maximum pH in all grain sizes occurs at 70 oC and 1.95 wt.% HCl and equals 6.7. The R square, adjusted R square, and predicted R square of the models are acceptable values and show that experimental data agrees with prediction data.